Reduction of Image Transmission Resources and Improvement In Image Security Using SPIHT, Fractional Fourier Transform and RSA Algorithm - Shaık Afsar Basha, Dr. Ayyem Pillai V (International Journal of Advanced Science and Technology, 2020)
Medical images require large amount of resources for transmission and storage. Over the last few years, due to increase in popularity of medical imaging applications, it is very important to minimize both storage and the transmission bandwidth for communication of data. The resources can be minimized by using compression. Security of medical images is also very important. So it is essential to find a secure and effective approach to transmit the data over the networks. One of the best suitable solutions for secure transmission is encryption of medical image data. Discrete Fractional Fourier Transform (DFRFT) is used for reducing the dimensions of an image. Wavelet decomposition is used for the image Compression and RSA algorithm for encryption and decryption of image. In this paper novel approach is used which combines SET PARTIONING IN HIERARCHIAL TREES (SPIHT) and RSA for the image encryption and compression which enhances both the security and transmission rate. All the results are simulated in MATLAB software Keywords: Block Based Pass-Parallel SPHIT,Fractional Fourier Transform (FRFT), Mean Square Error, Peak Signal To Noise Ratio (PSNR)